2019
DOI: 10.1142/s021827181943003x
|View full text |Cite
|
Sign up to set email alerts
|

Can fermionic dark matter mimic supermassive black holes?

Abstract: We analyze the intriguing possibility to explain both dark mass components in a galaxy: the dark matter (DM) halo and the supermassive dark compact object lying at the center, by a unified approach in terms of a quasi-relaxed system of massive, neutral fermions in general relativity. The solutions to the mass distribution of such a model that fulfill realistic halo boundary conditions inferred from observations, develop a highly-density core supported by the fermion degeneracy pressure able to mimic massive bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Our results provide strong observational support to the quantum-core hypothesis as an alternative to the massive BH hypothesis in Sgr A* (Argüelles et al 2019b(Argüelles et al , 2018, and also to the fermionic nature of DM. In this line, it is desirable to further test the presence of fermionic DM concentrations in our galactic core from existing luminosity constraints on the variability of the compact radio source Sgr A*, in addition to the dynamical constraints.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Our results provide strong observational support to the quantum-core hypothesis as an alternative to the massive BH hypothesis in Sgr A* (Argüelles et al 2019b(Argüelles et al , 2018, and also to the fermionic nature of DM. In this line, it is desirable to further test the presence of fermionic DM concentrations in our galactic core from existing luminosity constraints on the variability of the compact radio source Sgr A*, in addition to the dynamical constraints.…”
Section: Discussionsupporting
confidence: 73%
“…As was explicitly shown in Argüelles et al (2019bArgüelles et al ( ,a, 2018, this type of dense core -diluted halo density profile suggests that the DM might explain the mass of the dark compact object in Sgr A* as well as the halo mass. It applies not only to the Milky Way, but also to other galactic structures from dwarfs and ellipticals to galaxy clusters (Argüelles et al 2019a).…”
Section: Ruffini-argüelles-rueda Model Of Dark Mattersupporting
confidence: 64%
See 1 more Smart Citation
“…( 18) is thus solved numerically with a Levenberg-Marquardt least square minimization method, implying a large iterative process (taking ∼ few 10 1 hours of standard desktop CPU-time). below), since it is similar to that of a Milky-Way RAR DM halo for 𝑚𝑐 2 = 48 keV, shown to perfectly fit the rotation curve data (Argüelles et al 2018(Argüelles et al , 2019bBecerra-Vergara et al 2020). This is a remarkable result, since for the first time a core-halo solution like (3) known to be of astrophysical applicability, has now been proven to fall inside the meta-stable branch while being extremely long-lived (as calculated in appendix A) and thus reachable in Nature.…”
Section: Tidally Truncated Dm Halosmentioning
confidence: 64%
“…We believe this is not a coincidence: i.e. the fact that in Argüelles et al (2018Argüelles et al ( , 2019b; Becerra-Vergara et al (2020) it was shown the existence of a DM core-halo profile where the core can mimic a massive BH while the outer halo can explain the rotation curve, was already a smoking gun for its plausibility in Nature. (iii) There is a full family of solutions in the second stable branch between (b) and (c) (corresponding to 𝜃 0 ≈ 31.5 and 𝛽 0 ∈ [3.3 × 10 −5 , 5 × 10 −5 ]), which are found to be of astrophysical interest: that is, they lie within the allowed DM surface density Σ obs 0D strip as shown in fig.…”
Section: Tidally Truncated Dm Halosmentioning
confidence: 95%